Petrology and Petrography of Tuffaceous Sandstones from The Cipacar and Genteng Formations in the Kadurahayu Area, Lebak Regency, Banten Province, Indonesia - Salsabila Salsabila; Dwi Vina Febrim; Harnani Harnani (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2026)
This study analyzes the petrological characteristics and depositional mechanisms of tuffaceous sandstones in the Genteng and Cipacar Formations, located in the Kadurahayu area, Banten Province. By integrating field observations with quantitative petrography based on Pettijohn (1975), the research identifies distinct mineralogical and textural variations between the two units. The Early-Middle Pliocene Genteng Formation is classified as a lithic wacke, comprising quartz (25%), lithic fragments (28%), and volcanic glass (10%). In contrast, the Late Pliocene Cipacar Formation is categorized as a greywacke, characterized by higher volcanic glass (13%) and clay matrix (22%) content. The presence of massive structures, matrix-supported fabrics, and poor microscopic sorting indicates that these deposits originated from sediment gravity flows and subsequent volcaniclastic reworking rather than primary air-fall processes. Early diagenesis is marked by the devitrification of volcanic glass into clay minerals, which significantly influenced rock porosity and overall properties. Regionally, the Genteng Formation exhibits higher textural maturity due to more extensive transport and reworking, while the Cipacar Formation reflects distal volcanic facies with a dominant primary volcanic input. These findings enhance the understanding of the depositional processes and volcanostratigraphic evolution within the Java volcanic arc.